Nutritional dual burden in Indigenous young adults: The geographical differential. (30th January 2019) - Davison, Belinda; Goodall, Jennifer; Whalan, Sarah; Montgomery‐Quin, Kathleen; Howarth, Timothy; Singh, Gurmeet
Abstract: Objective: Nutritional dual burden is defined as the coexistence of underweight and overweight in the same population. We report the rates of nutritional dual burden in Indigenous young men and women in the Northern Territory. Additionally, we examine the impact geographical area has on these rates. Design: Cross‐sectional data obtained from the longitudinal Aboriginal Birth Cohort Study. Setting: Participants residing in over 40 urban and remote communities across the Top End of the Northern Territory. Participants: Young adults aged 23–28 years; urban ( n = 99) and remote ( n = 316). Main outcome measure(s): Anthropometric data was directly collected using standardised methods. Underweight was defined as BMI ≤ 18.5 kg/m 2 and overweight/obese as body mass index ≥ 25 kg/m 2 . Remote residency was categorised by established shires/regions (Vic/Daly, Arnhem and Tiwi). Results: Significantly higher levels of underweight were seen in remote participants, compared to urban participants, irrespective of sex. Further differences were seen by regions, with the highest rates seen in Vic/Daly, compared to Arnhem and Tiwi. Higher rates of overweight/obesity were found in urban participants, compared to remote. The levels of overweight/obesity varied, depending on region of residence. Conclusion: Underweight and overweight patterns coexist in Indigenous young adults, with variation across geographical regions. Health programs need to take this dual nutritional burden into consideration to avoid worsening the severity of underweight, whilst reducing levels of overweight.